2012
DOI: 10.1111/j.1365-2133.2012.10811.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous features of pseudoxanthoma elasticum in a patient with generalized arterial calcification of infancy due to a homozygous missense mutation in theENPP1gene

Abstract: Summary Background Pseudoxanthoma elasticum (PXE) manifests with cutaneous lesions consisting of yellowish papules coalescing into plaques of inelastic skin. Histopathology demonstrates accumulation of pleiomorphic elastic structures with progressive mineralization. The classic form of PXE is caused by mutations in the ABCC6 gene. Objectives A 2-year old patient with PXE of the neck, inguinal folds and lower abdomen, and with extensive tissue mineralization was evaluated for the underlying mutations in cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…As previous studies have suggested that MGP is a powerful antimineralization factor that has a role in PXE, these results suggested that reduction in the g-carboxylation of MGP as a result of warfarin treatment allowed progressive mineralization to ensue. Thus, patients with PXE may be at risk for increased ectopic mineralization and severity of their disease as a result of warfarin therapy (Li et al, 2012c).…”
Section: Pathomechanistic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies have suggested that MGP is a powerful antimineralization factor that has a role in PXE, these results suggested that reduction in the g-carboxylation of MGP as a result of warfarin treatment allowed progressive mineralization to ensue. Thus, patients with PXE may be at risk for increased ectopic mineralization and severity of their disease as a result of warfarin therapy (Li et al, 2012c).…”
Section: Pathomechanistic Pathwaysmentioning
confidence: 99%
“…It should also be noted that there has been a report of one family in which one of the siblings died in infancy with clinical findings consistent with GACI, whereas another sibling developed late-onset manifestations of PXE, which was subsequently shown to be associated with mutations in the ABCC6 gene (Le Boulanger et al, 2010). A related observation attesting to the clinical overlap of PXE and GACI is in a report describing a 2-year-old patient with clinical findings of vascular calcification consistent with GACI, and with characteristic cutaneous findings of PXE (Li et al, 2012c). This patient was shown to harbor mutations in the ENPP1 gene.…”
mentioning
confidence: 92%
“…On the other hand, patients with evidence of vascular mineralization due to mutations in the ENPP1 gene have been shown to depict skin findings clinically and histopathologically similar to those found in PXE. 17 Finally, there is a report of a family in which one of the brothers died early in life from extensive mineralization clinically diagnosed as GACI, while an older brother with mutations in the ABCC6 gene developed typical features of PXE later in life. 18 The reasons for this sort of extensive phenotypic variability in patients with the same pathogenic mutations in the ABCC6 and ENPP1 genes are currently unknown, but genetic modifier genes, epigenetic modulation, and environmental as well as lifestyle variables have been suggested to be contributing factors.…”
Section: Introductionmentioning
confidence: 99%
“…administration of PPi was found to inhibit vascular mineralization in rats and mice with experimentally induced renal failure; however, the short plasma half-life and lack of a suitable dosage form make PPi an unattractive candidate for supplementation therapy in humans (47,48). Treatment with bisphosphonates, a class of nonhydrolyzable PPi analogs, has been reasonably successful in GACI patients (49,50), but data are lacking for PXE patients (35,51). Alternatively, administration of the hypothetical factor X could be a potential cure for PXE.…”
mentioning
confidence: 99%